Simultaneously Enhanced Permeability and Selectivity of Pebax-1074-Based Mixed-Matrix Membrane for CO2 Separation - Rujing Hou; Junwei Xie; Yawei Gu; Lei Wang; Yichang Pan (Membranes)
Membrane technology is a promising methodology for carbon dioxide separation due to its benefit of a small carbon footprint. However, the trade-off relationship between gas permeability and selectivity is one obstacle to limiting its application. Herein, branched polyethyleneimine (BPEI) containing a rich amino group was successfully grafted on the surface of the metal–organic framework (MOF) of AIFFIVE-1-Ni (KAUST-8) through coordination between N in BPEI and open metal sites in the MOF and with the resultant maintained BET surface area and pore volume. Both the strengthened CO2 solubility coefficients coming from the additional CO2 adsorption sites of amino groups in BPEI and the reinforced CO2 diffusivity coefficients originating from the fast transport channels created by KAUST-8 led to the promising CO2 separation performance for KAUST-8@BPEI/Pebax-1074 MMM. With 5 wt.% KAUST-8@BPEI loading, the MMM showed the CO2 permeability of 156.5 Barrer and CO2/N2 selectivity of 16.1, while the KAUST-8-incorporated MMM (5 wt.% loading) only exhibited the CO2 permeability of 86.9 Barrer and CO2/N2 selectivity of 13.0. Such enhancement is superior to most of the reported Pebax-1074-based MMMs for CO2 separation indicating a wide application for the coordination method for MOF fillers with open metal sites.